Implementation of amplitude-integrated electroencephalography in tertiary Canadian Neonatal Intensive Care Units—a longitudinal study. Issue 8 (10th October 2019) - Grass, Beate; Crosdale, Blondel; Keyzers, Matthew; Deshpande, Poorva; Hahn, Cecil; Ly, Linh G; McNamara, Patrick J
Abstract: Aim: To investigate the implementation of amplitude-integrated electroencephalography (aEEG) as bedside monitoring tool of cerebral function in tertiary Canadian Neonatal Intensive Care Units (NICU) over the past decade. Methods: Longitudinal study consisting of online surveys of neonatologists on the use of aEEG in 2009 and 2018. Results: The response rate to the survey was 72 of 149 (49%) in 2009 and 18 of 30 (60%) in 2018, respectively. aEEG has been implemented in almost all (2009: 62.5%; 2018: 94%) tertiary Canadian NICUs. Two-thirds (2009: 67%; 2018: 71%) of the respondents considered information from aEEG tracing helpful in clinical practice. The main indications for aEEG were term neonates with hypoxic ischemic encephalopathy (2009 and 2018: 76%) and seizure detection/surveillance (2009: 88%; 2018: 94%). Teaching on aEEG has been implemented for neonatologists (2018: 100%) and health care providers (2018: 50%) in tertiary Canadian NICUs but there is a lack of standardization of training. Use of aEEG in preterm neonates (2009: 37%, 2018: 33%) and application of aEEG in research (18% reported occasional use) is less common. Conclusion: aEEG is well established in tertiary Canadian NICUs to monitor cerebral function and detect seizure activity. There is a need to develop formalized aEEG training programs and methods to assess competence. Further implementation of aEEG in preterm neonates and research is desirable.